Factors That Influence The Success Of XYZ E-Commerce Using Delone And Mclean Model: A Systematic Literature Review - Edwin Edwin*; Sfenrianto Sfenrianto (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
XYZ is a retail B2C e-commerce subsidiary of ASD group. XYZ provides home living and furniture goods such as kitchen equipment, furniture, electronics, etc. XYZ is established since 2016 and has already served 2,5 million customers and 5000 daily average orders since then. However, not all customers have positive experience in using XYZ to purchase their needs. This is caused by various factors in XYZ IS and business. Therefore, this research will discover the factors that significantly impact the success of XYZ using the latest DeLone and McLean IS Success Model. This Systematic Literature Review aims to study variables and indicators used in similar previous research to enrich the indicators obtained from survey results to XYZ customers. The results of this Systematic Literature Review are variables and indicators that will be used to measure this study, and there is 1 new indicator specific to this study, namely Personalized Service Quality. The discovery of this new indicator is based on the services offered by XYZ where customers can choose service methods according to customer convenience.